The costs of providing antiretroviral therapy services to HIV-infected individuals presenting with advanced HIV disease at public health centres in Dar es Salaam, Tanzania: Findings from a randomised trial evaluating different health care strategies. - Godfather Dickson Kimaro; Sayoki Mfinanga; Victoria Simms; Sokoine Kivuyo; Christian Bottomley; Neil Hawkins; Thomas S Harrison; Shabbar Jaffar; Lorna Guinness; REMSTART trial team (PLoS ONE)
Background Understanding the costs associated with health care delivery strategies is essential for planning. There are few data on health service resources used by patients and their associated costs within antiretroviral (ART) programmes in Africa. Material and methods The study was nested within a large trial, which evaluated screening for cryptococcal meningitis and tuberculosis and a short initial period of home-based adherence support for patients initiating ART with advanced HIV disease in Tanzania and Zambia. The economic evaluation was done in Tanzania alone. We estimated costs of providing routine ART services from the health service provider's perspective using a micro-costing approach. Incremental costs for the different novel components of service delivery were also estimated. All costs were converted into US dollars (US$) and based on 2012 prices. Results Of 870 individuals enrolled in Tanzania, 434 were enrolled in the intervention arm and 436 in the standard care/control arm. Overall, the median (IQR) age and CD4 cell count at enrolment were 38 [31, 44] years and 52 [20, 89] cells/mm3, respectively. The mean per patient costs over the first three months and over a one year period of follow up following ART initiation in the standard care arm were US$ 107 (95%CI 101-112) and US$ 265 (95%CI 254-275) respectively. ART drugs, clinic visits and hospital admission constituted 50%, 19%, and 19% of the total cost per patient year, while diagnostic tests and non-ART drugs (co-trimoxazole) accounted for 10% and 2% of total per patient year costs. The incremental costs of the intervention to the health service over the first three months was US$ 59 (p<0.001; 95%CI 52-67) and over a one year period was US$ 67(p<0.001; 95%CI 50-83). This is equivalent to an increase of 55% (95%CI 51%-59%) in the mean cost of care over the first three months, and 25% (95%CI 20%-30%) increase over one year of follow up.